Pengaruh Kualitas Produk, Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan Service pada Dealer Honda PT. Kembang Dwi Lestari di Mengwi, Badung - Ayu Puspa Yanti, Ni Putu Cening; Suartina, I Wayan; Atim Purwaningrat, Putu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The purpose of this study is to determine the effect of product quality, service quality and price on customer service satisfaction at Honda Dealer PT. Kembang Dwi Lestar in Mengwi. The number of subscribers in this study is 1,377 subscribers in 2022, so the number of respondents can be determined by the Slovin formula, so there are no less than 93 respondents. Sampling method with purposive sampling method and data collection method with observation, interview, literature and questionnaire distribution. The data analysis techniques used are multiple linear regression analysis, determination coefficient analysis, F test and t test. The results of the analysis show that product quality has a partial positive and significant effect on consumer satisfaction, so hypothesis 1 is accepted. Service quality partially has a positive and significant effect on customer satisfaction, so hypothesis 2 is accepted. Price partially has a positive and significant effect on customer satisfaction, so hypothesis 3 is accepted, and product quality, service quality and price have a significant effect on customer satisfaction simultaneously, so hypothesis 4 is accepted. Suggestions that researchers can give include routinely checking the quality of spare parts in stock and training vehicle maintenance workers to improve their skills or abilities in performing service and PT. Kembang Dwi Lestari in Mengwi, Badung has prepared a brochure of spare part product types and a list of vehicle services at complete prices.